Cardiometabolic risk factors and social jetlag in university professors - D.M.L. Galeno; H.J.A. Peixoto; B.T.S. Carneiro; M.A. Leocadio-Miguel (Brazilian Journal of Medical and Biological Research, 2023)
Chronic stress leads to circadian disruption, with variability in sleep time and duration. This scenario increases the prevalence and incidence of cardiometabolic abnormalities. Social jetlag (SJL), a proxy of circadian disruption, has been associated with increased vulnerability to the development of metabolic syndrome, obesity, and type 2 diabetes. This research aimed to evaluate how variables associated with cardiometabolic risk are related to SJL and poor sleep among university professors. From 2018 to 2019, full-time university professors (n=103) with a mean age of 44±5.4 years were assessed for sleep quality, chronotype, SJL, metabolic components, sociodemographic characteristics, and physical evaluation. Sleep quality and weekday sleep duration were associated with stress (r=0.44 and r=-0.34) and anxiety (r=0.40), respectively. Mean sleep duration (n=65) was 7.0±1.1 h and all professors with poor sleep (41.2%; n=28) worked 40 h/week. Professors who slept less were significantly (r=-0.25) older, and teaching time (years) was positively correlated with blood glucose (r=0.42). Mean SJL was 59.8 ±4.5 min (n=68) and 48.5% of these professors had values ≤1 h and 51.4% ≥1 h. SJL and blood glucose concentration were associated (r=0.35), which reinforced that challenges to the circadian system reverberate on metabolism. In this study, professors at the Federal University of Rio Grande do Norte had cardiometabolic risks related to anxiety, stress, and sleep quality.